Short-term food deprivation does not improve the efficacy of a fish oil finishing strategy in Murray cod - Giorgio Palmeri; Giovanni Turchini; S De Silva (2009)
Two groups of fish ( Maccullochella peelii peelii ) were fed for a 90-day conditioning period on a canola oil diet (CO) or a fish oil diet (FO). Canola oil diet fed fish were then shifted to the FO diet for a 90-day finishing period. A variable period of starvation (0, 5, 10 and 15 days) was introduced to reduce the initial lipid level of CO fed fish at the beginning of the finishing period and therefore accelerate the rate of recovery of FO-like fatty acids. During starvation, fish did not show significant reduction in total lipid content, either in the fillet or whole body. At the end of the conditioning period, fatty acid composition of the diet was mirrored in fish tissues. These differences came close to levelling out following re-feeding, with the exception of n - 6 polyunsaturated fatty acids (PUFA). However, no effects of the starvation periods on the final fatty acid make-up of fish were recorded. The results of this trial show that Murray cod, when subjected to a starvation period of up to 15 days, does not lose an appreciable quantity of lipid and, therefore, the tested starvation approach to reduce the initial level of lipid has to be considered unsuccessful.